Canadian physiotherapists' views on certification, specialisation, extended role practice, and entry-level training in rheumatology - Sutton Evelyn; Westby Marie D; Li Linda C; Thompson Marlene; Sayre Eric C; Casimiro Lynn (BMC, 2009)
Abstract Background Since the last decade there has been a gradual change of boundaries of health professions in providing arthritis care. In Canada, some facilities have begun to adopt new arthritis care models, some of which involve physiotherapists (PT) working in extended roles. However, little is known about PTs' interests in these new roles. The primary objective of this survey was to determine the interests among orthopaedic physiotherapists (PTs) in being a certified arthritis therapist, a PT specialized in arthritis, or an extended scope practitioner in rheumatology, and to explore the associated factors, including the coverage of arthritis content in the entry-level physiotherapy training. Methods Six hundred PTs practicing in orthopaedics in Canada were randomly selected to receive a postal survey. The questionnaire covered areas related to clinical practice, perceptions of rheumatology training received, and attitudes toward PT roles in arthritis care. Logistic regression models were developed to explore the associations between PTs' interests in pursuing each of the three extended scope practice designations and the personal/professional/attitudinal variables. Results We received 286 questionnaires (response rate = 47.7%); 258 contained usable data. The average length of time in practice was 15.4 years (SD = 10.4). About 1 in 4 PTs agreed that they were interested in assuming advanced practice roles (being a certified arthritis therapist = 28.9%, being a PT specialized in rheumatology = 23.3%, being a PT practitioner = 20.9%). Having a caseload of ≥ 40% in arthritis, having a positive attitude toward advanced practice roles in arthritis care and toward the formal credentialing process, and recognizing the difference between certification and specialisation were associated with an interest in pursing advanced practice roles. Conclusion Orthopaedic PTs in Canada indicated a fair level of interest in pursuing certification, specialisation and extended scope practice roles in arthritis care. Future research should focus on the effectiveness and cost-effectiveness of the emerging health service delivery models involving certified, specialized or extended scope practice PTs in the management of arthritis.